Uncertainty and Compensation Design in Strategic Interfirm Contracts. (14th November 2019) - Krishnan, Ranjani; Mani, Deepa
ABSTRACT: In strategic outsourcing contracts, a substantial portion of implementation occurs at the client's premises and requires integration of effort between the vendor and the client. Compensation design in such contracts involves trade‐offs between the higher (lower) incentive properties of fixed‐price (cost‐plus) contracts and their higher (lower) ex ante contracting and ex post adaptation costs. Uncertainty influences these trade‐offs and affects compensation design. We explore the compensation implications of two types of uncertainty—volatility and ambiguity—which are reflected in the client's accounting measures. Volatility reflects the unpredictability of changes in the future environment, which makes it difficult to contractually specify future contingencies. Ambiguity reflects lack of consensus about the nature, drivers, and value effects of uncertainty, which makes it difficult to contractually specify responses to contingencies if and when they occur. Volatility increases the likelihood of ex post adaptation costs, while ambiguity increases ex ante contracting costs; therefore, volatility and ambiguity decrease the attractiveness of fixed‐price contracts. We use accounting and market measures to calibrate volatility and ambiguity and examine their implications for compensation design and ex post renegotiation. Analysis of archival data for 455 strategic outsourcing contracts valued over 15 million indicates that volatility and ambiguity influence contract compensation design and renegotiation likelihood. These results hold even after controlling for asset specificity, task complexity, and relational factors. We conclude that accounting measures can provide signals of volatility and ambiguity and thereby influence compensation design in strategic interfirm contracts. RÉSUMÉ: Incertitude et conception de la rémunération dans les contrats stratégiques intersociétés Dans les contrats stratégiques d'impartition, une part importante de l'exécution s'effectue dans les locaux du client et exige la conjugaison des efforts du vendeur et du client. La conception de la rémunération dans de tels contrats nécessite des compromis entre les propriétés incitatives supérieures (inférieures) des contrats à prix fixe (à coût majoré) et les coûts supérieurs (inférieurs) associés aux contrats établis ex ante et à l'adaptation ex post. L'incertitude influe sur ces compromis et a une incidence sur la conception de la rémunération. Les auteures analysent les répercussions qu'ont sur la rémunération deux formes d'incertitude, la volatilité et l'ambiguïté, se reflétant dans les mesures comptables du client. La volatilité découle de l'imprévisibilité de l'évolution des conditions, ce qui rend difficile la formalisation contractuelle des éventualités. L'ambiguïté découle de l'absence de consensus quant à la nature et aux inducteurs de l'incertitude, ainsi que de son incidence sur la valeur, ce qui complique la formalisation contractuelle des réactions aux éventualités lorsqu'elles surviennent, le cas échéant. La volatilité hausse la probabilité de coûts d'adaptation ex post, alors que l'ambiguïté hausse les coûts de l'établissement de contrats ex ante; par conséquent, la volatilité et l'ambiguïté rendent plus attrayants les contrats à prix fixe. Les auteures utilisent des mesures comptables et des mesures du marché pour calibrer la volatilité et l'ambiguïté et en étudier les conséquences pour la conception de la rémunération et la renégociation ex post. L'analyse de données d'archives relatives à 455 contrats stratégiques d'impartition d'une valeur supérieure à 15 millions de dollars révèle que la volatilité et l'ambiguïté influent sur la conception de la rémunération contractuelle et la probabilité de renégociation. Ces résultats persistent même une fois contrôlés la spécificité des actifs, la complexité de la tâche et les facteurs relationnels. Les auteures concluent que les mesures comptables peuvent fournir des indicateurs de volatilité et d'ambiguïté et, de ce fait, influer sur la conception de la rémunération dans les contrats stratégiques intersociétés.